LINGUOCULTURAL ANALYSIS OF SOMATIC PHRASEOLOGICAL UNITS OF ENGLISH AND KARAKALPAK LANGUAGES: LINGUOCULTURAL ANALYSIS OF SOMATIC PHRASEOLOGICAL UNITS OF ENGLISH AND KARAKALPAK LANGUAGES - Doshanova, Kamila (Журнал иностранных языков и лингвистики, 2025)
Linguocultural analysis of somatic phraseological units involves examining how specific expressions related to the body reflect cultural values, beliefs, and practices in different languages. In this case, we'll explore English and Karakalpak languages. Somatic phraseological units are idiomatic expressions that incorporate body parts or functions to convey meanings beyond their literal interpretations. These expressions often reveal insights into cultural attitudes, social norms, and cognitive frameworks.